The City Experience with Location-Based Media: An Examination Through Cognitive Maps - IAVARONE, AYŞENUR HİLAL; HASGÜL, ESİN; BAŞAR, EROL (Konya Technical University, 2021)
Purpose The physical space has been an important value for supporting human experience. With the development of mobile devices and location-based media, these technologies have been increasingly present in our virtual spatial experience and the experience of physical city has been changed permanently. Accordingly, this paper aims to discuss the experience potential of urban space with location-based technologies. Design/Methodology/Approach The research structure of this study is based on the literature of location-based media and 'Space of flow' theory. Within the methodology, a workshop is conducted to review the cognitive mappings of the virtual city experience. The workshop is structured through two segments: Documenting the spatial experience revealed using location-based media made by cognitive mappings and testing participants' direct experiences within structured questionnaire-based interviews and finally, interpretating of the obtained data. Findings This paper provides an experiential examination of the relationship between the usage of the degree of location-based media and cognitive experience. Findings point out that experience may differ depending on the media interface used and it is controversial comparing with the physical space experience with its multiple relationships. Research Limitations/Implications The research subject had been exemplified with limited location-based media in a specific location. Originality/Value The proposed method of examining the degree of spatial experience by the location-based media linking with interviews determines the originality of the study. There are also limited studies on the topic of location-based media by focusing on the users' cognitive maps.
Keywords: Urban Space; Virtual City Experience; Spatial Cognition; Location-Based Media; Cognitive-Mapping